Faktor-Faktor Terjadinya Pernikahan Siri dan Akibat Hukumnya menurut Undang-Undang Perkawinan - Novi Dian Pratiwi; Umi Salamah; Fauzi Muhammad; Ayub Mursalin (AKADEMIK: Jurnal Mahasiswa Humanis, 2026)
Unregistered marriage (commonly known as siri marriage) remains a prevalent social and legal phenomenon in Indonesia, despite clear statutory requirements mandating official marriage registration. This practice persists due to a combination of religious interpretations, cultural traditions, economic constraints, and societal pressures that lead couples to prioritize religious validity over legal recognition. This study aims to examine siri marriage from a normative legal perspective and to analyze its legal implications within the Indonesian legal system. The research employs a qualitative approach using normative legal research methods, with library research as the primary data source. The unit of analysis focuses on the practice of siri marriage in Indonesia. Data were collected through an extensive review of legal literature, including books, scholarly journals, and relevant laws and regulations, particularly Law No. 1 of 1974 on Marriage. Data analysis was conducted using a juridical-qualitative method by identifying, classifying, and interpreting legal materials to achieve a comprehensive understanding of the issue. The findings indicate that siri marriages are not legally recognized by the state, resulting in significant legal consequences, such as the absence of legal protection for wives, uncertainty regarding the legal status of children, and difficulties in resolving disputes related to divorce and child custody. Therefore, marriage registration is essential to ensure legal certainty and the protection of individual rights. Increased public awareness and improved accessibility of marriage registration procedures are crucial to addressing this issue.